Outrageous women: a comparison of five passages within the canonical passion and empty tomb narratives emphasizing the role of women - Taylor, Birgit (Department of Religious Studies, 2014)
This dissertation seeks to further develop the existing appreciation of the role of women around Jesus, by analysing selected texts within the canonical passion and empty tomb narratives. One of the issues that will be explored concerns the historicity and significance of the canonical empty tomb tradition, in which women are portrayed as the primary witnesses to the empty tomb and the resurrection. By tracing the history and the development of five selected texts within the canonical passion and empty tomb narratives, this dissertation will explore the role and function of women around Jesus. In addition, I will endeavour to motivate the inclusion and portrayal of women in these canonical texts based on a comparison of the treatment of these women by the canonical gospel writers. In order to re-evaluate the significance of the illustrated behaviour of women in the canonical passion and empty tomb narratives, five texts will be examined, beginning with the tradition of the woman anointing Jesus. The actions described in these texts will be situated within the socio-cultural context of first-century Palestine and compared to the funerary customs prevalent in Ancient Judaism. Furthermore the historicity and transmission history of these texts will be examined by applying both redaction criticism and tradition history to the texts. This dissertation will demonstrate that the tradition of the woman anointing Jesus and the tradition at the empty tomb depict behaviour, which is contrary to the culturally expected conduct of women regarding funerary customs within Ancient Judaism. However. the texts containing women's activities before. during and immediately after the passion narratives illustrate conduct. that corresponds to the customary mourning practices. Redactional analyses of the texts further indicate the awkwardness of portraying women as credible witnesses within the androcentric character of the patriarchal culture in first-century Palestine. This dissertation argues that. in terms of the criterion of cultural dissimilarity. the anointing tradition and the empty tomb tradition are most likely based on early forms of the traditions emerging during the oral period. This suggests strongly that women were the first witnesses to the empty tomb.